Trends in outcomes, complications and readmission rates in patients undergoing transcatheter aortic valve implantation: a nationwide analysis from 2012 to 2019. (3rd October 2022) - Goel, A; Malik, A; Bandyopadhyay, D; Gupta, R; Hajra, A; Krishnan, A M; Singhal, M; Ahmad, H
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has evolved over the years from a procedure requiring surgical vascular access and general anesthesia, to one that can be completed entirely percutaneously with conscious sedation. Advancement in procedural techniques and operator experience has resulted in better outcomes for patients undergoing TAVI. Purpose: The purpose of our study was to analyze the trends over the years in outcomes, complications and unplanned readmission rate in patients undergoing TAVI. Methods: The United States Nationwide Readmission Database for the years 2012 to 2019 was queried to identify all adult patients who underwent elective TAVI. The primary outcome of the study was inpatient mortality during TAVI hospitalization. Secondary outcomes included periprocedural complications (like acute kidney injury, bleeding requiring transfusion, need for permanent pacemaker implantation, stroke), length of stay, hospitalization cost, and unplanned 30-day readmission rate. Appropriate International Classification of Diseases (ICD-9 and ICD-10) codes were used to identify comorbidities and complications. Results: A total of 283, 409 patients who underwent TAVI were included in the study. The baseline characteristics of these patients are shown in picture 1. The inpatient mortality during TAVI admission declined steadily and significantly from 5.3% in the year 2012 to 0.0% in the year 2019 (p value for trend <0.001). There was a significant reduction in peri-TAVI occurrence of acute kidney injury (from 18.1% in 2012 to 8.7% in 2019), bleeding requiring transfusion (from 28.0% in 2012 to 4.3% in 2019), and stroke (from 1.8% in 2012 to 0.1% in 2019) (p value for trend <0.001 for all). Periprocedural conduction abnormalities requiring permanent pacemaker implantation increased from 7.4% in 2012 to 12.1% in 2015, before coming down to 8.9% in 2019 (p value for trend <0.001). The mean length of hospital stay and inflation-adjusted costs during admission for TAVI decreased from 9.6 days and 64, 695 in the year 2012, to 3.6 days and 49, 710 in the year 2019, respectively (p value for both <0.001). The unplanned 30-day all-cause readmission rate after TAVI also reduced steadily and significantly from 18.2% in 2012 to 11.5% in 2019 (p value <0.001). Conclusion: Over the years, there has been a significant reduction in inpatient mortality, periprocedural complications (such as acute kidney injury, need for blood transfusion, stroke), length of hospital stay, and inflation-adjusted hospital costs in patients undergoing transcatheter aortic valve implantation. Furthermore, there has been a significant decline in the 30-day unplanned readmission rate after transcatheter aortic valve implantation. Funding Acknowledgement: Type of funding sources: None.